The Influence of Motivation, Authentic Leadership, and Organizational Culture on Employee Performance in the South Bengkulu Health Office - Pratama, Dio Raga; Suryosukmono, Gerry (SENTRALISASI, 2024)
This research aims to examine the impact of motivation, authentic leadership, and organizational culture on employee performance at the South Bengkulu Health Service. The population in this study were all employees at the South Bengkulu Health Service. The method used in this research is a quantitative method, and data collection uses a questionnaire with a purposive sampling method for 120 respondents. Data was processed through validity and reliability tests with SEM-PLS. The results of the analysis show that motivation, authentic leadership and organizational culture have a positive and significant influence on employee performance. These findings provide an important contribution to the development of management strategies in the context of healthcare organizations.